Sensory Ganglia-Specific TNF Expression Is Associated With Persistent Nociception After Resolution of Inflammation - Gonçalves, William Antonio; Rezende, Barbara Maximino; Oliveira, Marcos Paulo Esteves de; Ribeiro, Lucas Secchim; Fattori, Victor; Silva, Walison Nunes da; Prazeres, Pedro Henrique Dias Moura; Queiroz-Junior, Celso Martins; Santana, Karina Talita de Oliveira; Costa, Walyson Coelho; Beltrami, Vinícius Amorim; Costa, Vivian Vasconcelos; et al. (Frontiers in Immunology, 2020)
Joint pain is a distressing symptom of arthritis, and it is frequently persistent even after treatments which reduce local inflammation. Continuous production of algogenic factors activate/sensitize nociceptors in the joint structures and contribute to persistent pain, a challenging and difficult condition to treat. TNF is a crucial cytokine for the pathogenesis of several rheumatic diseases, and its inhibition is a mainstay of treatment to control joint symptoms, including pain. Here, we sought to investigate the inflammatory changes and the role of TNF in dorsal root ganglia (DRG) during persistent hypernociception after the resolution of acute joint inflammation. Using a model of antigen-induced arthritis, the peak of joint inflammation occurred 12–24 h after local antigen injection and was characterized by an intense influx of neutrophils, pro-inflammatory cytokine production, and joint damage. We found that inflammatory parameters in the joint returned to basal levels between 6 and 8 days after antigen-challenge, characterizing the resolving phase of joint inflammation. Mechanical hyperalgesia was persistent up to 14 days after joint insult. The persistent nociception was associated with the inflammatory status of DRG after cessation of acute joint inflammation. The late state of neuroinflammation in the ipsilateral side was evidenced by gene expression of TNF, TNFR2, IL-6, IL-1β, CXCL2, COX2, and iNOS in lumbar DRG (L3-L5) and leukocyte adhesion in the lumbar intumescent vessels between days 6 and 8. Moreover, there were signs of resident macrophage activation in DRG, as evidenced by an increase in Iba1-positive cells. Intrathecal or systemic injection of etanercept, an agent clinically utilized for TNF neutralization, at day 7 post arthritis induction, alleviated the persistent joint hyperalgesia by specific action in DRG. Our data suggest that neuroinflammation in DRG after the resolution of acute joint inflammation drives continuous neural sensitization resulting in persistent joint nociception in a TNF-dependent mechanism.